MAHASISWA DAN NILAI UNIVERSAL DEMOKRASI: PELUANG DAN TANTANGAN DALAM MENGHADAPI THREE EASY PATHS TO REGRESSION - Elkristi Ferdinan Manuel (Fakultas Hukum Universitas Gunung Rinjani, 2025)
Abstract This research shows that the role of students in the whirlpool of times in Indonesia greatly impacts social life. Historical facts prove that students could overthrow the government during the time of President Sukarno, and President Soeharto. The student movement from time to time turned out to have its characteristics, whereas, during the old order period, freedom of opinion at that time grew with academic nuances and ideologies that developed until finally close to the government, thus causing demonstrations at the end of the government period. The New Order period had authoritarian characteristics where the government exerted military power on the campus such as the MALARI Incident and the NKK/BKK Policy. During this period, students can finally overthrow the government. The challenges of post-reform are very different, where currently freedom of expression is protected by laws and regulations, but the challenges come from the side of social media that is fueled by disinformation and internal threats to are critical in facing the three paths of regression as stated by Charles Taylor, namely the Three Easy Pats to Regression. The third path of regression of democracy is the first is to emphasize inequality, which is the path to regression through increasing inequality by forming spirals that eat themselves. The second path is exclusion, in which various exclusive collective identities marginalize some of the other groups, thus hindering solidarity and participation and creating polarization in society. And the third path is to define the people against